" In Yugoslavia, everything was viewed through the prism of nationalism" an interview with Croatian philosopher Zarko Puhovski - Puhovski, Zarko (IP / Global edition, 2009)
In 1989 and 1990, change was in the air of socialist Yugoslavia, too. But things looked very different from in the Soviet-led East bloc. The population demanded democracy and free elections in their respective republics. This put the multinational state on path to war. (DGAP-IP)